How to Support The Algebraic Thinking Skills of Elementary School Students Using The Generative Multi-Representation Learning Model Modification Schema-Based Instruction? - Evi Faujiah; Yurniwati Yurniwati; Gusti Yarmi (Jurnal Elementaria Edukasia, 2024)
Elementary school teachers still do not fully utilize effective learning models, especially in teaching algebraic concepts. Lack of understanding of algebraic concepts has caused students to have difficulty mastering algebra, including calculation, representation, and mathematical modeling, as well as recognizing algebraic symbols and variables. The purpose of this study is to answer the research question (RQ) How does the Generative Multi Representation Learning Model Modified Schema Based Instruction (MGMRM-SBI) affect the algebraic thinking skills of elementary school students? In this study, the experimental method was used with a posttest-only control group design, where the sample was selected using Cluster Random Sampling with a total sample of 128 students. The research instrument used was an algebraic thinking ability test in the form of description test questions, and data analysis was carried out using a t-test with the help of SPSS statistical software. The results of the t-test showed a significant difference between the algebraic thinking skills of students in the experimental and control classes, with significance values (2 sides) = 0.000 < sig. = 0.05. Based on the results of the study, it can be concluded that the application of the Generative Multi Representation Learning model Modified Schema Based Instruction has a significant effect on the algebraic thinking ability of elementary school students, and is more effective than the expository model.